2011
DOI: 10.1002/asna.201111516
|View full text |Cite
|
Sign up to set email alerts
|

First detection of a magnetic field in the fast rotating runaway Oe star ζ Ophiuchi

Abstract: The star ζ Ophiuchi is one of the brightest massive stars in the northern hemisphere and was intensively studied in various wavelength domains. The currently available observational material suggests that certain observed phenomena are related to the presence of a magnetic field. We acquired spectropolarimetric observations of ζ Oph with FORS 1 mounted on the 8-m Kueyen telescope of the VLT to investigate if a magnetic field is indeed present in this star. Using all available absorption lines, we detect a mean… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 46 publications
0
21
0
2
Order By: Relevance
“…Later, the star was monitored by the MOST satellite, which revealed at least a dozen significant pulsation frequencies between 1 and 10 d −1 , typical of β Cep-like pulsation modes (Walker et al 2005). The first detection of a mean longitudinal magnetic field in this star was announced by Hubrig et al (2011c). Nine additional FORS 2 spectropolarimetric observations showing a change of polarity have been obtained over all four observing nights.…”
Section: ζ Ophmentioning
confidence: 96%
“…Later, the star was monitored by the MOST satellite, which revealed at least a dozen significant pulsation frequencies between 1 and 10 d −1 , typical of β Cep-like pulsation modes (Walker et al 2005). The first detection of a mean longitudinal magnetic field in this star was announced by Hubrig et al (2011c). Nine additional FORS 2 spectropolarimetric observations showing a change of polarity have been obtained over all four observing nights.…”
Section: ζ Ophmentioning
confidence: 96%
“…Hubrig et al (2011c) have reported the detection of a magnetic field at just over the 3σ level in the runaway O-type star ζ Oph = HD 149757. Our re-reduced measurement of this star no longer shows a significant field.…”
Section: O-type Starsmentioning
confidence: 99%
“…Gamma2 Velorum (γ 2 Vel) is a binary system with a large spectral contribution from the Wolf-Rayet star (Millour et al 2007). Zeta Ophiuchi (ζ Oph) is a magnetic star of O e -type (Hubrig et al 2011). Alpha Virginis (α Vir) is a double-lined spectroscopic binary (B1V+B4V) with an ellipsoidal variation of 0.03 mag due to tidal distortion (Harrington et al 2009).…”
Section: A Revised Sbc Relation For Late-and Early-type Starsmentioning
confidence: 99%